EMPOWERMENT OF ECOREGIONS AS THE MANAGEMENT CULTURE OF THE ORGANIZATION - SETIA TJAHYANTI; NURTI WIDAYATI; IAN NURPATRIA SURYAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
Community economy activities that depend on natural resources but without damaging the natural resources named Green Economics, where the economy activities may take the form of mining activities, land use and other forest areas. It is also governed by Law no. 40/2007 on limited liability Company in sections 74 subsection (1) requires that any company which is engaged in businesses that rely on the natural resources it required to carry out the social and environmental responsibility. It thereby apply not only to companies rely on natural resources but also that business activities impact on the environment company. In this case cultural organization could help solve the problems of external adaptation and integration an organization. All economic activities of organizations if relying on natural resources then should be based on ecoregions where every natural resource exploration activities must go through the stages of AMDAL. Through empowerment culture good organization and right, then can avoid abuse sense of basic constitution of the Republic of Indonesia the 1945 constitution, article 33 paragraph (3), pertaining to concept state right of control and for optimal public welfare.